Dexmedetomidine as an adjunct to bupivacaine and xylocaine with adrenaline in ultrasound guided supraclavicular brachial plexus block in upper limb surgeries - Shrestha, Alisha; Shrestha, Abhisesh; Shrestha, Anil; Piya, Roshan; Pradhan, Manisha; Amatya, Shirish Prasad; Hirachan, Niroj; Ghimire, Binam (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Supraclavicular brachial plexus block is widely used for perioperative anesthesia and analgesia. Dexmedetomidine is highly selective alpha-2 receptor agonist which provides analgesia, sedation and anxiolysis. Our study aims to evaluate the effect of addtion of dexmedetomidine with bupivacaine and xylocaine with adrenaline in supraclavicular block in upper limb surgeries. Method: This was a comparative study conducted at Patan Hospital, Patan Academy of Health Sciences, Nepal among 44 patients randomly assigned in Group-I (N=22, bupivacaine and xylocaine with adrenaline 28 ml + dexmedetomidine 2 ml (1 mcg/kg), and Group-II (N=22, without dexmedetomidine) for ultrasound-guided supraclavicular block for upper limb surgeries. The study was approved by institutional review committee. Onset of sensory and motor block, duration of analgesia, demographics, hemodynamic parameters, and side effects of drug were compared. Pin-prick test and modified Bromage scale were used to evaluate sensory and motor block. Visual analogue scale was used for severity of pain. Statistical analysis was performed with SPSS v.16. Result: The median time for onsets of sensory and motor block were significantly shorter in group I (1 m and 3 m) than group II (5 m and 10 m). The duration of analgesia was s longer in group I (720 m) than group II (360 m). Two patients had bradycardia and one hypertension in dexmedetomidine group whch were managed successfully. Conclusion: Dexmedetomidine added to local anesthetics significantly prolongs the effect of supraclavicular block in upper limb surgeries.